2006
DOI: 10.1073/pnas.0604494103
|View full text |Cite|
|
Sign up to set email alerts
|

The mediator complex functions as a coactivator for GATA-1 in erythropoiesis via subunit Med1/TRAP220

Abstract: The Mediator complex forms the bridge between transcriptional activators and RNA polymerase II. Mediator subunit Med1/TRAP220 is a key component of Mediator originally found to associate with nuclear hormone receptors. Med1 deficiency causes lethality at embryonic day 11.5 because of defects in heart and placenta development. Here we show that Med1-deficient 10.5 days postcoitum embryos are anemic but have normal numbers of hematopoietic progenitor cells. Med1-deficient progenitor cells have a defect in formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 43 publications
7
99
0
1
Order By: Relevance
“…In the present study, we showed that Mediator subunit Med1 is essential for erythroid development and correct induction of β-globin gene expression. As shown previously by others and us, Med1 is an important coactivator for the master regulator GATA-1 (9,10,28). Whereas other GATA factors have been shown to be essential for T-cell development (GATA-3) or hematopoietic stem cells (GATA-2) (as reviewed in ref.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, we showed that Mediator subunit Med1 is essential for erythroid development and correct induction of β-globin gene expression. As shown previously by others and us, Med1 is an important coactivator for the master regulator GATA-1 (9,10,28). Whereas other GATA factors have been shown to be essential for T-cell development (GATA-3) or hematopoietic stem cells (GATA-2) (as reviewed in ref.…”
Section: Discussionmentioning
confidence: 92%
“…GATA-1 interacts with multiple co-regulators (31), including FOG-1 (14,32), CREB-binding protein (CBP)/p300 (33), MED1 (34), and BRG1 (27,28), and all except MED1 have been shown to occupy the LCR (27,28,35,36). We tested whether ER-GATA-1 occupancy at the LCR and promoter is coupled to co-regulator recruitment at these sites.…”
Section: Progressive Assembly Of a Cell Type-specific Chromatin Loopmentioning
confidence: 99%
“…FOG-1 facilitates GATA-1 chromatin occupancy (14,15) and interacts with the nucleosome remodeling and deacetylase (NuRD) chromatin remodeling complex (16) containing the ATPase CHD4 (Mi2β), which is required for development of erythroid and other hematopoietic lineages (17,18). GATA-1 also recruits the chromatin remodeler BRG1 (19,20), the histone acetyltransferase CBP/p300 (21), and the mediator complex component Med1 (22,23). BRG1 promotes expression of adult α-and β-like globin genes in erythroid cells (19,24), CBP/p300 mediates GATA-1 function in at least certain contexts (21), and Med1 amplifies GATA-1 activity at select target genes (22).…”
mentioning
confidence: 99%